2022
DOI: 10.3354/ab00754
|View full text |Cite
|
Sign up to set email alerts
|

Life history of spinyhead croaker Collichthys lucidus (Sciaenidae) differentiated among populations from Chinese coastal waters

Abstract: Otolith microchemistry provides valuable information about the environmental history of individual fish, but few studies have considered the influence of population or stock on life history traits. This study used the Sr/Ca ratio as an index of habitat use of spinyhead croaker Collichthys lucidus from 2 different populations (northern and southern China populations), including lifetime otolith microchemistry profiles (n = 63 fish) and determinations of natal habitat selection (n = 352 fish). The otolith data r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…The suitable salinity range in autumn was wide, ranging between 13 and 34 (Figure 4). Many studies have shown the characteristics of C. lucidus tolerance to a wide range of salinities [44], but Liu [45] reported that the buoyancy of fish eggs and the development of juveniles are closely related to the salinity of the habitat. A high-salinity water environment is often needed to stimulate parent spawning, reproduction and early juvenile growth.…”
Section: Effects Of Marine Variables On the Distribution Of C Lucidus...mentioning
confidence: 99%
“…The suitable salinity range in autumn was wide, ranging between 13 and 34 (Figure 4). Many studies have shown the characteristics of C. lucidus tolerance to a wide range of salinities [44], but Liu [45] reported that the buoyancy of fish eggs and the development of juveniles are closely related to the salinity of the habitat. A high-salinity water environment is often needed to stimulate parent spawning, reproduction and early juvenile growth.…”
Section: Effects Of Marine Variables On the Distribution Of C Lucidus...mentioning
confidence: 99%